Pengembangan Metode Analisis Senyawa Antioksidan dalam Buah Naga Merah Menggunakan Spektrofotometri UV-VIS - Abriyani, Ermi; Valentina, Della Putri; Kurniawati, Iin; Mudrikah, Siti; Amelia, Tanti (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this literature review article is to determine "Development of a Method for Analysis of Antioxidant Compounds in Red Dragon Fruit Using UV-Vis Spectrophotometry". This method is important for measuring red dragon fruit antioxidants to determine antioxidant activity which has health benefits such as anti-aging and protection. The Literature Review method used in this research is Systemic Literature Review (SLR). The data used in the research were obtained from the Google Scholar database, Sci-Hub Journal, PubMed, Science directe, Publish or perish with the keywords analytical method, red dragon fruit, UV-Vis Spectrophotometry. Based on research from journal reviews, it can be concluded that several articles Supporting this, it shows that the UV-VIS spectrophotometry method meets the validation criteria and can be used to measure the antioxidant activity of various types of extracts.